De novo frameshift mutation in SYNGAP1 resulting in autosomal dominant mental retardation type 5 and autism spectrum disorder: a case report - Lin, Shuangzhu; Qi, Yangfan; Xie, Hongyan; Sun, Xiaoyu; Wang, Wanqi; Jiang, Kai (Frontiers in Pediatrics, 2025)
BackgroundAutosomal Dominant Intellectual Disability Type 5 (MRD5) is caused by heterozygous mutations in the SYNGAP1 gene. This gene, located on chromosome 6q21, encodes a synaptic Ras/Rap GTPase-activating protein that regulates Ras/Rap signaling and AMPA receptor trafficking, impacting synaptic plasticity and neuronal homeostasis. According to studies by Chen et al. and Kim et al., the SYNGAP1 gene is localized to dendritic spines of pyramidal neurons in the rodent neocortex.Case summaryWe report a 2-year-10-month-old girl presenting with global developmental delay (GDD) and autistic behaviors, characterized by unsteady gait, inability to stand on one foot, significantly impaired expressive language (maximally three-word phrases), poor response to name, reduced eye contact, and absent joint attention, despite normal hearing. Standardized assessments revealed severe impairments: Gesell Developmental Quotient (DQ) = 36, Childhood Autism Rating Scale (CARS) score = 42 (indicating severe autism), and Autism Diagnostic Observation Schedule (ADOS-2) Module 1 score = 16. Whole-exome sequencing identified a de novo heterozygous frameshift mutation in the SYNGAP1 c.1230delC p. (Ser410ArgfsTer30), classified as pathogenic per ACMG guidelines. Electroencephalography (EEG) revealed no abnormalities, and brain magnetic resonance imaging (MRI) showed no structural lesions. The patient was diagnosed with MRD5 and Autism Spectrum Disorder (ASD).ConclusionWe present a case of SYNGAP1-related MRD5 characterized by significant global developmental delay and autism spectrum disorder, featuring a novel c.1230delC frameshift variant that has not been reported before. This discovery expands clinicians' knowledge of the mutation spectrum and phenotypic variability linked to SYNGAP1, enhancing understanding of genotype-phenotype relationships in SYNGAP1-related conditions.